2008
DOI: 10.1179/135100008x259240
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dynamic hand-grip exercise on acetone in gas emanating from human skin

Abstract: This study investigated the effects of dynamic hand-grip exercise on skin-gas acetone concentration. The subjects for this experiment were seven healthy males. In the first experiment, to ascertain the reproducibility of the results for the skin-gas acetone concentration test, the skin gas was collected four times from one subject. In the second experiment, all subjects performed three different types of exercise (Exercises I-III) for a duration of 60 s. Exercise I was performed at 10 kg with one contraction e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…We reported in a previous study that the acetone concentration emanating from skin increased with hand-grip exercise. 11 When the total work of hand-grip exercise was the same, acetone concentration in skin gas was related to exercise intensity, but not to frequency of exercise. 11 The results of our study basically agreed with those of others.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We reported in a previous study that the acetone concentration emanating from skin increased with hand-grip exercise. 11 When the total work of hand-grip exercise was the same, acetone concentration in skin gas was related to exercise intensity, but not to frequency of exercise. 11 The results of our study basically agreed with those of others.…”
Section: Discussionmentioning
confidence: 93%
“…10 We reported that skin-gas acetone concentration increased with hand grip exercise. 11 No other reports have been published regarding the influence of cycle exercise on acetone concentration in skin gas. This study, consequently, investigated the influence of dynamic cycle exercise on expired air and skin-gas acetone concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Reported skin released acetone levels ranged from 0.2 ppm to 1.2 ppm (here values changed with exercise) [11]. These values correlate linearly to exhaled acetone which ranged from (0.5 to 4 ppm) [11]. Clearly, both sources skin and exhale provide the same order of magnitude levels, which emphasized the detectability of skin released acetone.…”
Section: Validaɵonmentioning
confidence: 90%
“…Monitoring of skin released acetone has closely followed methods for monitoring acetone in breath; skin released acetone is sampled by a plastic bag and gas chromatography or ion flow tube spectroscopy were used to measure its concentration [6], [7]. Reported skin released acetone levels ranged from 0.2 ppm to 1.2 ppm (here values changed with exercise) [11]. These values correlate linearly to exhaled acetone which ranged from (0.5 to 4 ppm) [11].…”
Section: Validaɵonmentioning
confidence: 99%
“…Sasaki et al (2011) reported that acetone concentration in expired air increased during graded and prolonged exercise such as walking or running. We have reported that acetone concentrations emanated from skin gas and in expired air increased with high exercise intensities of cycle exercise (Yamai et al 2009) and hand-grip exercise (Mori et al 2008). …”
Section: Introductionmentioning
confidence: 99%